Doctoral research on cadastral development - Cagdas, Volkan; Stubkjaer, Erik (ELSEVIER SCI LTD, 2009)
The multitude of rights in land and the recording of these rights are addressed by a number of studies, yet a recognized paradigm for such studies seems missing. Rights in land are recorded and managed through either cadastral systems or land administration systems depending on the legal system of the countries concerned. The cadastre, however, is the core of both systems as it provides for systematic and official descriptions of land parcels or real property units. The research mentioned often has a development perspective, and in this article we will motivate the introduction of the research domain of cadastral development. This research is multi-disciplinary and draws on elements of theories and methodologies from the natural, the social, the behavioral, and the formal sciences. During the last decade or so, doctoral dissertations have come to constitute a substantial part of this research effort. The article focuses on the methodological aspect of doctoral research by analyzing ten doctoral dissertations. Our analysis is based on a taxonomy of methodological elements and aims at identifying commonalities and differences among the dissertations in the use of concepts and methods. Having completed the main analysis, we invited the authors of the dissertations to comment upon our analysis of their work and the developed taxonomy. The responses corroborate the view that the taxonomy could be used for further analyses and provide for a framework for further doctoral research. The article concludes with a call for a shared terminology and a shared set of concepts which may contribute to further theory building within the cadastral domain. (C) 2008 Elsevier Ltd. All rights reserved
Keywords: Cadastre; Cadastral development; Cadastral system; Doctoral research; Land administration; Land registration; Land tenure; Property rights; Research methodology; Theory building; Environmental Sciences & Ecology